1972
DOI: 10.1149/1.2404171
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Grown-ln and Process-Induced Defects in Single Crystal Silicon

Abstract: Distributions of defects observed in single crystals of silicon grown from the melt are shown to be congruent with two well known growth inhomogeneities characterized either by a spiral ramp pattern or a faceted core pattern in the crystal. The consequences of these defects are traced through the oxidation of the substrate, as required for a subepitaxial diffusion, and (after removal of the oxide) the growth of an epitaxial layer. It will be shown that the defect distributions persist through these processes a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

1972
1972
2002
2002

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…We have, however, schematically outlined the problem as shown in Fig. 5, which is based, in part, on recent work of Pomerantz (17) and de Kock (8,18,19).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have, however, schematically outlined the problem as shown in Fig. 5, which is based, in part, on recent work of Pomerantz (17) and de Kock (8,18,19).…”
Section: Discussionmentioning
confidence: 99%
“…It is well established (8,17) that metallic imPurities introduced during stage II processing can become associated with stage I defects to form stacking faults during oxidation or epitaxial growth. This type of process-induced defect is most certainly gettered by the POGO misfit dislocation and/or phosphorus diffusion treatment itself.…”
Section: Discussionmentioning
confidence: 99%
“…[134][135][136][137][138][139] The defects distribute in a swirl pattern, reflecting the combined effects of melt convection, rotation of the crystal and temperature fluctuations at the crystal-melt interface during crystal growth. The observed defects reflect conditions subsequent to the complete crystal growth process, resulting from the complicated set of microscopic defect reactions in silicon.…”
Section: Dislocation-free Crystal Growthmentioning
confidence: 99%
“…(18)(19)(20)(21). Although a number of workers have shown that stacking faults are produced in the atmospheric silicon epitaxial layer during thermal oxidation (22)(23)(24)(25)(26), none has reported the oxidation-induced Key words: gettering, tensile stress, bow of wafer, oxidationinduced stacking fault.…”
mentioning
confidence: 99%